Do Consumers Always Spend more when Coupon Face Value is Larger? The Inverted U-Shaped Effect of Coupon Face Value on Consumer Spending Level. (July 2018) - Jia, He (Michael); Yang, Sha; Lu, Xianghua; Park, C. Whan
Commonly, a coupon can be applied to one of several vertically differentiated products sold at different prices within the same product line of a brand. With such a product-line coupon, consumers need to decide on the specific product to buy, resulting in different levels of consumer spending. One field data set and four lab experiments demonstrate that the relationship between coupon face value and consumer spending level may not always be intuitively positive; under certain circumstances, it could take an inverted U-shape. The authors develop a threshold-based model to explain the inverted U-shaped effect of coupon face value on consumer spending level and show that this effect occurs when the price level of products is high, when consumers have a strong saving orientation, when they experience low information load from processing a small number of products, when they are inclined to engage in thorough product comparison, or when they have a weak preexisting preference for a specific level of product benefit.